Making Japanese Thought More Intelligible to the West. Arūnas Gelūnas Interviews Thomas P. Kasulis - Vilnensia 2005 6 (1), Acta Orientalia Orientalia (Acta Orientalia Vilnensia, 2005)
Arūnas Gelūnas Interviews Thomas P. Kasulis